1987
DOI: 10.1016/0014-5793(87)80428-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of the Ca2+‐ATPase of skeletal muscle sarcoplasmic reticulum Inhibition by myotoxin a

Abstract: Decavanadate produces extensive ordered arrays of Ca 2+-ATPase molecules on sarcoplasmic reticulum (SR) vesicle surfaces [(1984) J. Bioenerg. Biomembranes 16, 491-505] and the basic unit of these crystalline structures seems to be a dimer of Ca 2 +-ATPase [(1983) J. Ultrastruct. Res. 24, 454-464; (1984) J. Mol. Biol. 174, 193-204]. Myotoxin a, isolated from the venom of the prairie rattlesnake Crotalus viridis viridis, is a muscle-degenerating polypeptide and its primary site of interaction is the SR membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Binding in this region would have to be such as not to affect binding of ATP, since neither the ATPdependence of ATPase activity nor the rate of phosphoenzyme formation are affected (results not shown). It has also been reported that inhibition of the ATPase by myotoxin a and decavanadate are non-competitive [56], suggesting that myotoxin a does not bind close to the phosphate-binding site on the ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…Binding in this region would have to be such as not to affect binding of ATP, since neither the ATPdependence of ATPase activity nor the rate of phosphoenzyme formation are affected (results not shown). It has also been reported that inhibition of the ATPase by myotoxin a and decavanadate are non-competitive [56], suggesting that myotoxin a does not bind close to the phosphate-binding site on the ATPase.…”
Section: Discussionmentioning
confidence: 99%